2019
DOI: 10.21203/rs.2.19624/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pattern of Fasting Blood Sugar, Blood Pressure and Body Mass Index among Combined Oral Contraceptive (COC) Pills Users in Chencha, Southern Ethiopia: a cross-sectional study

Abstract: Background: The use of contraceptives has become prevalent among women in Ethiopia. Oral contraceptive use has been suggested to trigger changes in glucose metabolism, energy expenditure, blood pressure, and body weight, among the various populations and ethnic groups. Objective: To elucidate the pattern of fasting blood sugar (FBS), blood pressure and body mass index (BMI) among combined oral contraceptive (COC) pills users, taking into account other confounding factors including socioeconomic conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results additionally showed that there was a reduction in the degree of HDL-C in ladies taking the prophylactic pill contrasted with the control group [18]. Preventative pills can prompt weight acquire [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…The results additionally showed that there was a reduction in the degree of HDL-C in ladies taking the prophylactic pill contrasted with the control group [18]. Preventative pills can prompt weight acquire [25,26].…”
Section: Resultsmentioning
confidence: 99%